Environmental Communication in Indigenous Communities: Education for Environmental Management - Domínguez González, Nancy; Cruz Vázquez, Miguel; Tetla Tepixtle, Mireya; Martínez Sánchez, José Alberto; Soto Pol, Viridiana Rosabelhi; Ayala Benitez, David Omar (Emerging Trends in Education, 2021)
This research presents a systemic scheme to develop environmental communication based on a theoretical proposal regarding the characteristics to consider for it to be effective, according to its objectives of informing, educating, and promoting changes in attitudes and values consistent with the conservation and/ or restoration of the environment. Its importance lies in the environmental problems we face as a society and in the need to establish effective mechanisms to inform and train a society more responsible for its environment. Following the case study methodology, we analyze the dissemination strategies corresponding to three environmental management projects carried out in indigenous rural communities where Totonaco or Náhuatl are spoken as the first language and Spanish as the second language. The trends observed made it possible to prove the premises of the theoretical proposal, and the relevance of the proposed scheme to develop environmental communication, as well as the areas of opportunity to achieve communication processes focused on sensitizing the indigenous population on the importance of collaboratively building solutions to the environmental problems they face.